A new species of Cretodorus (Hemiptera: Fulgoromorpha: Fulgoroidea: Mimarachnidae) from Upper Cretaceous amber of northern Myanmar. (December 2021) - Zhang, Xiao; Yao, Yunzhi; Ren, Dong; Pang, Hong
Abstract: A new species of Mimarachnidae, Cretodorus rostellatus sp. nov., with well-preserved male genitalia is described from the Upper Cretaceous (lowermost Cenomanian) Burmese amber. Diagnostic features of the genus Cretodorus are reviewed. The paedomorphic nature of this family are discussed, including sensory pits, median carinae, tarsal segment.